Trans-disciplinary Research: An Academic-Practitioner Partnership Effort on Investigating the Relationship between the Cooperative Model and Sustainability - Robert Newell; Ann Dale; Yuill Herbert; Fiona Duguid; Rebecca Foon; Peter Hough (RIMCIS, 2015)
This article details novel research methodology developed through a researcher-practitioner partnership and employed in a three-phase research effort that explored relationships between the co-operative model and sustainable development. Firstly, a basic understanding of the characteristics of the co-operative model was established using the co-operative principles as a framework, and their complementarity to sustainable development was examined by comparing them with sustainability theory, principles and best practices (defined through seminal journal articles on the topic). Secondly, relationships between sustainability theory and the ideas and operations of currently functioning co-operatives were investigated, namely, whether co-operatives had integrated sustainability into their organizations. Thirdly, an integrated analysis that examined the relationship between co-operatives, the co-operative principles and sustainability concepts was conducted, and output from this work was used to build a visualization (referred to as the ‘Co-operative Star’), specifically designed to communicate a synthesis of research findings to diverse audiences. This study specifically focused on co-operatives and sustainability; however, the analytical techniques developed and employed have applications for other research involving comparisons between concepts and large bodies of literature, and it is particularly useful for comparing theoretical works (such as academic literature) with texts that discuss operations and practices (such as website and reports).